Community-Based Health Promotion Programs: Innovations for Sustainable Preventive Care - Rini Ambarwati; Minarti Minarti; Nur Hasanah; Benny Novico Zani (Journal of World Future Medicine, Health and Nursing, 2025)
Growing concern over rising rates of preventable diseases and disparities in access to healthcare has intensified the need for innovative community-based health promotion models that support long-term preventive care. Sustainable preventive strategies increasingly rely on community engagement, participatory education, and context-sensitive interventions capable of addressing social, behavioral, and environmental determinants of health. This study aims to examine how innovative approaches within community-based health promotion programs can strengthen preventive practices and enhance community resilience. A mixed-methods design was employed, integrating survey data from program participants, in-depth interviews with community health workers, and field observations conducted across three urban and rural intervention sites. The findings reveal that community-driven innovations such as culturally tailored health education, peer-led initiatives, and locally adapted preventive tools significantly improve health literacy, encourage sustained behavioral change, and expand access to preventive resources. The programs demonstrated enhanced community ownership, stronger intersectoral collaboration, and measurable. The study concludes that community-based health promotion programs, when supported by innovative and participatory frameworks, serve as an effective pathway toward sustainable preventive care.